The application of manipulatatives-mediated reciprocal teaching in Grade 10 Science class - Ciego, Chermagne Marielle D.; Porlares, Charl Vince I. and Proceso, Sharalyn G. 4 0 16; 5 (2016)
ABSTRACT: The purpose of the study is to investigate the effectiveness of Manipulatives- mediated Reciprocal Teaching in the understanding of science concepts in Grade 10. The study focuses on the effectiveness of manipulatives and the positive influences of reciprocal teaching. The data was collected using test questionnaires, a pre-test and post-test method. The results obtained were analyzed using different statistical treatments to find out the significant difference between variables. Research findings offered a positive result in terms of the learning outcome and understanding of science concept. There was a below average level of student understanding and after the method was applied there was an increased in the level (above average). It is furthermore supported by the result in the analyses using Correlated t-Test. There was a significant difference between the initial testing and the post-testing in each treatment. However, there had been no significant differences in the level of student understanding among the three methods used in discussing the topic about the Endocrine System. The result actually supported the statement given by Ozckus (2013), When you use a variety of hand-on tools, reciprocal teaching becomes truly student centered, interactive, and memorable. This may possibly mean that reciprocal teaching method is not a stand-alone method used in teaching. It would be better if tools, like manipulatives, are incorporated when applying it.
Thesis: (Bachelor of Secondary Education with Specialization in Biological Sciences) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2